2013
DOI: 10.1371/journal.pone.0079194
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvants and Immunization Strategies to Induce Influenza Virus Hemagglutinin Stalk Antibodies

Abstract: The global population remains vulnerable in the face of the next pandemic influenza virus outbreak, and reformulated vaccinations are administered annually to manage seasonal epidemics. Therefore, development of a new generation of vaccines is needed to generate broad and persistent immunity to influenza viruses. Here, we describe three adjuvants that enhance the induction of stalk-directed antibodies against heterologous and heterosubtypic influenza viruses when administered with chimeric HA proteins. Addavax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
66
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(70 citation statements)
references
References 24 publications
1
66
2
Order By: Relevance
“…Although low levels of antibodies-and immunological memory-are associated with protection from mortality, it is questionable whether these low antibody titers have a protective effect against morbidity. Therefore, a strategy, possibly based on prime-boost regimens and/or more effective adjuvants (36)(37)(38), to induce long-term immunity may be needed for a successful stalk-based universal influenza virus vaccine. Another interesting question is how broadly reactive the antibody response induced by sequential vaccination would be.…”
Section: Discussionmentioning
confidence: 99%
“…Although low levels of antibodies-and immunological memory-are associated with protection from mortality, it is questionable whether these low antibody titers have a protective effect against morbidity. Therefore, a strategy, possibly based on prime-boost regimens and/or more effective adjuvants (36)(37)(38), to induce long-term immunity may be needed for a successful stalk-based universal influenza virus vaccine. Another interesting question is how broadly reactive the antibody response induced by sequential vaccination would be.…”
Section: Discussionmentioning
confidence: 99%
“…We previously demonstrated that the 5=pppRNA sequence can be rationally modified to maximize the RIG-I response, leading to high expression of many proinflammatory and antiviral genes (24). Among the PRR-stimulating adjuvants, 5=pppRNA molecules, TLR agonists, defective interfering RNA produced by Sendai virus, and baculovirus-based vaccination vectors have all been utilized as adjuvants in several vaccine formulations, yielding promising data in preclinical studies (35,(43)(44)(45)(46)(47). Unfortunately, widespread implementation of PRR-based adjuvants in vaccines has been hampered by safety concerns, as infections and innate responses can sometimes be linked to autoimmune diseases (15).…”
Section: Discussionmentioning
confidence: 99%
“…To determine whether M8 possessed adjuvant activity in an in vivo model of vaccination, BALB/c mice were vaccinated by intramuscular injection with VLP coexpressing the HA and NA from H5N1 and HIV Gag protein, in combination with M8, M5, or poly(I·C) (which was previously shown to potentiate responses to influenza virus antigens [35]). Three weeks later, mouse sera were collected and analyzed for HAI activity (hemagglutination inhibition assay [HAI] or receptor blocking titers); mice immunized with VLP adjuvanted with M8, M5, or poly(I·C) displayed a 2-to 3-fold increase in HA-specific IgG titers (data not shown) and 2-to 3-fold-higher HAI antibody titers (P Ͻ 0.005) ( Fig.…”
Section: M8 Potentiates Influenza Vlp Immunogenicitymentioning
confidence: 99%
“…It is of note that DNA vaccination is not essential for induction of broad protection by cHA vaccination regimens. Vaccination with just proteins (no DNA) yielded results comparable to vaccination with DNA priming in earlier studies (18). Three weeks postprime, animals received a recombinant cH5/3 protein (H5 head derived from A/Vietnam/1203/04 on top of an H3 stalk derived from A/Perth/16/09) (16).…”
mentioning
confidence: 85%